2007
DOI: 10.1103/physrevlett.99.147401
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Trapped-Mode Resonances in Planar Metamaterials with a Broken Structural Symmetry

Abstract: We report that resonant response with a very high quality factor can be achieved in a planar metamaterial by introducing symmetry breaking in the shape of its structural elements, which enables excitation of dark modes, i.e. modes that are weakly coupled to free space. The exotic and often dramatic physics predicted for metamaterials is underpinned by the resonant nature of their response and therefore achieving resonances with high quality factors is essential in order to make metamaterials' performance effic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
812
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,104 publications
(835 citation statements)
references
References 15 publications
18
812
2
3
Order By: Relevance
“…One promising approach to decreasing radiative losses while maintaining finite coupling to free-space radiation is to utilize the phenomenon of Fano interference 35 originally introduced in atomic physics to describe asymmetrically shaped ionization spectral lines of atoms. More recently, the concept of Fano resonances was introduced to the field of photonics and metamaterials 23,28,[36][37][38][39] in which a photonic structure possesses two resonances generally classified as 'bright' (that is, spectrally broad and strongly coupled to incident light) and 'dark' (spectrally sharp, with negligible radiative loss). The weak nearfield coupling between the bright and dark resonances leads to coupling of the incident light to the dark resonance that maintains its low radiative loss, thereby remaining high-Q.…”
mentioning
confidence: 99%
“…One promising approach to decreasing radiative losses while maintaining finite coupling to free-space radiation is to utilize the phenomenon of Fano interference 35 originally introduced in atomic physics to describe asymmetrically shaped ionization spectral lines of atoms. More recently, the concept of Fano resonances was introduced to the field of photonics and metamaterials 23,28,[36][37][38][39] in which a photonic structure possesses two resonances generally classified as 'bright' (that is, spectrally broad and strongly coupled to incident light) and 'dark' (spectrally sharp, with negligible radiative loss). The weak nearfield coupling between the bright and dark resonances leads to coupling of the incident light to the dark resonance that maintains its low radiative loss, thereby remaining high-Q.…”
mentioning
confidence: 99%
“…The asymmetry comes from the close coexistence of resonant transmission and resonant reflection. Previous work has shown that a certain small structural (geometrical) asymmetry has to be introduced to the shape of their conducting elements to excite such resonances [2,3]. In our prior work we have shown that similar effects can be achieved without breaking the geometrical symmetry of the resonator but instead by introducing an electrical asymmetry through a combination of substrates with different dielectric properties [4].…”
Section: Introductionmentioning
confidence: 81%
“…The physics of coherent effects in -type three-level atoms is related to the excitation of the maximum coherence between two ground states (in alkali atoms, these are the hyperfine levels) under the condition when a special coherent state, the so-called dark state, is formed. EIT has been achieved in atomic [5,6,8] and molecular [34,35] gases, BECs [13], solid-state systems [36][37][38], metamaterials [39][40][41], and even the mechanical effect of light [42].…”
Section: Discussionmentioning
confidence: 99%